PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PADA KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - JULI SUARDANA, KADEK; SURYANAWA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis, 2010)
Researches on relationship between budget participation and managerial performance have shown inconclusive evidences. Therefore moderating variables are necessary. Organization commitment is one of these variables. High commitment makes individual doing his/her best for the success of the organization. This research is conducted in SKPD Offices in Badung Regency. The purpose is to investigate the effect of budget participation on managerial performance and to examine whether organization commitment can moderate the relationship between budget participation and managerial performance. Respondents consist of member of management, whether top, middle, and lower level. Sample is defined using purposive sampling technique. Result of the first hypothesis test shows that budget participation significantly and positively affects managerial performance. The second test results that organization commitment is not able to strengthen the relationship between budget participation and managerial performance. Some limitations of this research comprise the use of self rating scale on measurement of managerial performance, and the use of only one moderating variable. Further research could measure financial performance and also consider using other variables that expected to moderate the relationship between budget participation and managerial performance.
Keywords: participation, managerial performance, organization commitment.